2018
DOI: 10.1002/adfm.201806500
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Photocatalytic Ability of Cu2O Nanowires for CO2 Conversion by MXene Quantum Dots

Abstract: MXene quantum dots (QDs) are emerging 0D nanomaterials. Here, a new heterostructure is developed based on a 1D photoactive semiconductor and a 0D MXene QD for improved photocatalytic reduction of CO 2 into methanol. Specifically, Ti 3 C 2 QDs are incorporated onto Cu 2 O nanowires (NWs) through a simple self-assembly strategy. It is demonstrated that Ti 3 C 2 QDs not only significantly improve the stability of Cu 2 O NWs but also greatly improve their photocatatlytic performance by enhancing charge transfer, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
240
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(261 citation statements)
references
References 60 publications
7
240
0
Order By: Relevance
“…f) Photocatalytic performance for production of CH 4 of TiO 2 /Ti 3 C 2 T x catalysts. Reproduced with permission . Copyright 2018, Elsevier Ltd.…”
Section: Mxene‐based Catalysts For Photocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…f) Photocatalytic performance for production of CH 4 of TiO 2 /Ti 3 C 2 T x catalysts. Reproduced with permission . Copyright 2018, Elsevier Ltd.…”
Section: Mxene‐based Catalysts For Photocatalysismentioning
confidence: 99%
“…In additional to the 2D/2D heterojunction, MXenes‐based heterostructures with reduced dimensional were also developed for efficient CO 2 conversion. Zeng et al reported the 0D MXene quantum dots (QDs) derived from 2D Ti 3 C 2 MXene and their coupling with 1D Cu 2 O nanowires (NWs) for the 0D/1D heterostructures . The Ti 3 C 2 QDs/Cu 2 O NWs/Cu delivered a CH 3 OH yield of 153.38 ppm cm −2 , which was 2.15 times of that from Ti 3 C 2 sheets/Cu 2 O NWs/Cu and 8.25 times of that from Cu 2 O NWs/Cu.…”
Section: Mxene‐based Catalysts For Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Photocatalytic CO 2 reduction into chemical fuels powered by [1][2][3][4][5] Photocatalytic CO 2 reduction into chemical fuels powered by …”
Section: Introductionmentioning
confidence: 99%
“…The Mott-Schottky (MS) patterns of the nanocomposites are measured to investigate its at band potential and charge density, [44][45][46][47][48][49][50] as shown in Fig. 6c.…”
Section: Resultsmentioning
confidence: 99%